Aflatoxin biomarkers in human biological samples and their potential reduction by probiotic lactobacillus casei Shirota strain - Sabran, Mohd Redzwan (2014)
This thesis comprised of five main research projects, studied the presence of aflatoxin biomarkers in human biological samples and the use of probiotic Lactobacillus casei Shirota strain (LcS) as a potential aflatoxin adsorbent. The first research project involved a questionnaire survey among 160 subjects to assess their knowledge on fungal and aflatoxin contamination in the diets. More than half ofsubjects (n=84, 52.5%) participated in the screening stage had low level of knowledge. There were several significant findings between socio-demographic characteristics and subjects’ knowledge on fungal and aflatoxin contamination in the diets. In particular, being female and single and with personal income below RM1500 accounted for a significant 10.6% of the variability in the subjects’ overall ores of knowledge on fungal and aflatoxin contamination in the diets [R2=0.106,adjusted R2=0.089, F (2, 156)=6.154, p=0.001] and the personal income was found to be the sole determinant of subjects’ overall knowledge (β=-0.288, p=0.000). As for the second research project, morning urine samples were collected from the subjects for the measurement of Aflatoxin M1 (AFM1) using enzyme linked immunosorbent assay (ELISA) as well as to determine its association with the food consumption. Ninety-eight urine samples (n=98) were positive with AFM1. Only four from 37 food items in the food frequency questionnaire (FFQ) namely readyto- eat cereals (r=0.222, p=0.036), soybean milk (r=0.266, p=0.011), kuih kacang (r=0.222, p=0.035) and peanut butter (r=0.211, p=0.045) showed moderate and positive association with the levels of urinary AFM1. A significant association (φ=0.286) was found between the levels of urinary AFM1 and the consumption of milk and dairy products as subjects with intake of milk and dairy products greater than 67.78 g/day had significantly and higher urinary AFM1 levels. The estimated dietary Aflatoxin B1 (AFB1) exposure was 11.7 ng/day/ kg body weight,contributing to 0.29 cancer cases in 100, 000 populations where 6.1% of liver cancer could be attributable by aflatoxin exposure. The third research project pertained to the use of ultra high performance liquid chromatography (UHPLC) for the measurement of urinary AFM1. The UHPLC method was optimized and used to analyse urinary AFM1 among seventy-one subjects (n=71) recruited from 160 subjects that participated in the screening stage. Thirteen subjects (n=13) had detectable urinary AFM1 ranging from 2.4 to 100.34 pg/ml. As for the fourth research project, the study was conducted to determine the effectiveness of 4 weeks cross-over intervention study with fermented milk containing LcS in reducing the levels of aflatoxin biomarkers in human blood and urine samples. Seventy-one subjects (n=71) were divided into two groups namely Blue and Yellow group. Overall, the intervention did not significantly reduce the levels of serum AFB1-lysine adduct and urinary AFM1 as well as the liver and kidney biomarkers. Nonetheless, the potential of LcS as an aflatoxin adsorbent to a certain extent was observed in some subjects especially in the Blue group. Within 2 weeks of intervention, the levels of serum AFB1-lysine adduct reduced significantly from 6.24 ± 3.42 pg/mg albumin (ALB) to 5.14 ± 2.15 pg/mg ALB, with 17.63% of reduction. Although not significant (p=0.332), the levels of AFB1-lysine at the end of intervention (4th week) was lower compared to the baseline levels. As for the urinary AFM1 levels, a decreasing trend was observed over the 4 weeks of intervention. The fifth project was conducted to determine the effect of LcS on the bioaccessibility of AFB1 through an in vitro simulation of human digestion under fed condition. Peanut samples were artificially contaminated by spiking with two contamination levels of AFB1 namely 4.53 and 8.56 ng/g. The contaminated peanut samples were applied to the simulation model together with three treatments namely activated carbon, cultured LcS and probiotic drink containing LcS. The average AFB1 bioaccessibility of 83.92% from both spiked peanut samples with 4.53 ng/g and 8.56 ng/g indicated that AFB1 was released completely from the food matrix (i.e peanut samples). The addition activated carbon reduced greatly AFB1 bioaccessibility. By comparison, the addition of LcS (cultured LcS and probiotic drink containing LcS) did not produce a big reduction of AFB1 bioaccessibility as seen with the application of activated carbon. Nonetheless, the treatment to a certain extent decreased AFB1 bioacessibility about 20% especially in the peanut samples spiked with 8.56 ng/g AFB1.